Studi komparasi Model Guided Discovery learning dan Problem Based Learning terhadap kemampuan berpikir analitis siswa pada mata pelajaran Geografi - Rissa Permata Sari; Fatiya Rosyida; Hadi Soekamto; I Komang Astina; Eka Anita Putri (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
This study aims to determine differences in students' analytical thinking abilities using the Guided Discovery Learning model and the Problem Based Learning Model in Geography subject in high school. The ability to think analytically is important for students in learning geography because it is needed to analyze the spatial relations of a phenomenon. Discovery activities in this study made students gain new knowledge. The research is in the form of a quasi-experiment in the form of a posttest only control group design. This research was conducted at SMAN 4 Malang with a sample of X IPS 3 (experiment 1) and X IPS 4 (experiment 2) in the odd semester of 2022/2023. Measurement of analytical thinking ability through a description test according to indicators of analytical thinking ability. The data analysis technique used the t-test, previously the prerequisite tests were carried out, namely the normality and homogeneity tests. The results showed that there were differences in students' analytical thinking skills using the Guided Discovery Learning model and the Problem Based Learning model, this was indicated by the Sig. hypothesis test of 0.001 <0.05. The Guided Discovery Learning model is better than the Problem Based Learning Model for students' analytical thinking skills. This is evidenced by the average posttest score of experimental class 1 which received the learning treatment with the Guided Discovery Learning Model of 80.58. While the experimental class 2 which received the learning treatment with the Problem Based Learning Model obtained an average score of 72.71. Several factors influenced the average value of analytical thinking skills in experimental class 1 to be higher than in experimental class 2, namely the success of students in solving geographic problems through group investigations in the Guided Discovery Learning model and the aid of the learning media used, namely Sparkol Videoscribe. The application of the Guided Discovery Learning model and the Problem Based Learning Model requires a long time. Therefore, proper preparation and time management is required before implementation. Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan berpikir analitis siswa dengan menggunakan model Guided Discovery Learning dan Model Problem Based Learning pada mata pelajaran Geografi di SMA. Kemampuan berpikir analitis penting dimiliki siswa dalam pembelajaran geografi karena dibutuhkan untuk menganalisis relasi keruangan dari suatu fenomena. Kegiatan penemuan dalam penelitian ini membuat siswa mendapatkan pengetahuan baru. Penelitian berupa quasi experiment bentuk posttest only control group design. Penelitian ini dilaksanakan di SMAN 4 Malang dengan sampel X IPS 3 (eksperimen 1) dan X IPS 4 (eksperimen 2) pada semester ganjil 2022/2023. Pengukuran kemampuan berpikir analitis melalui tes uraian sesuai dengan indikator kemampuan berpikir analitis. Teknik analisis data menggunakan uji-t, sebelumnya dilakukan uji prasyarat yaitu uji normalitas dan homogenitas. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan berpikir analitis siswa dengan menggunakan model Guided Discovery Learning dan Model Problem Based Learning, hal ini ditunjukan dengan nilai Sig. uji hipotesis sebesar 0,001< 0,05. Model Guided Discovery Learning lebih baik dibandingkan Model Problem Based Learning terhadap kemampuan berpikir analitis siswa. Hal ini dibuktikan dengan rata-rata nilai posttest kelas eksperimen 1 yang mendapat perlakuan pembelajaran dengan Model Guided Discovery Learning sebesar 80,58. Sedangkan kelas eksperimen 2 yang mendapatkan perlakuan pembelajaran dengan Model Problem Based Learning memperoleh rata-rata nilai sebesar 72,71. Beberapa faktor yang mempengaruhi rata-rata nilai kemampuan berpikir analitis kelas eksperimen 1 lebih tinggi daripada kelas eksperimen 2 adalah keberhasilan siswa dalam memecahkan permasalahan geografi melalui penyelidikan kelompok pada model Guided Discovery Learning dan bantuan media pembelajaran yang diterapkan yaitu Sparkol Videoscribe. Penerapan model Guided Discovery Learning dan Model Problem Based Learning memerlukan waktu yang lama. Maka dari itu diperlukan persiapan dan pengelolaan waktu yang baik sebelum diimplementasikan.